EDUKASI DAN PENYULUHAN GEJALA SERTA PENGENDALIAN PENYAKIT BLAS DAN KRESEK TANAMAN PADI DI NAGARI SUNGAI DAREH, SUMATERA BARAT - Wisnubroto, Muhammad Parikesit; Suhendra, Dede; Edwin, Edwin (Universitas Mataram, 2024)
Nagari Sungai Dareh is a part of the Punjung Island District, West Sumatra which has a relatively flat topography and tropical climate. Most of the population works as farmers, so there are many rice planting areas. Problems faced by local farmers are blast and bacterial leaf blight disease attacks, while no appropriate control methods have been found. Therefore, this service was carried out which aims to increase farmers' knowledge about the symptoms and control of these two types of diseases. The equipment used in this activity includes stationery, projectors, presentation materials, and speakers. This service activity was carried out in 3 stages which included 1) Focus Group Discussion, 2) location survey and direct observation in rice cultivation fields, and 3) education and extension on the symptoms and control of blast and bacterial leaf blight diseases. During the presentation, farmers were enthusiastic in listening. Discussions took place well between the presenters and farmers. Blast disease is caused by the fungus Pyricularia oryzae, while bacterial leaf blight is caused by the bacterium Xanthomonas oryzae. Blast disease gives symptoms in the form of grayish-brown rhombic spots, while bacterial leaf blight symptoms are yellowing, pale, dry leaves starting from the tips, edges to spread to all parts of the leaf. Both diseases can be well controlled through the use of resistant varieties and improved cultivation techniques. The application of appropriate doses of N fertilizer can suppress blast and bacterial leaf blight attacks, because the higher the N applied causes the plant tissue to be softer, making it easily infected by fungi and bacteria. This activity succeeded in increasing farmers' knowledge about the symptoms of blast and crackle diseases and the best methods to suppress them.